FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR - PEDRO SUKMADIJAYA; IGNES JANUAR CAHYADI (Jurnal Bisnis dan Akuntansi, 2017)
The purposes of this research is to analyze the effect of managerial ownership, independent board of commissioners, audit committe, company size, return on equity, leverage and earnings per share to firm’s value. The achievement of value of the firm may effect positive impact, both internal and external’s company. The population is manufacture companies listed in Indonesian Stock Exchange from 2011-2015. This research use purposive sampling method to determine the sample and only 41 companies selected as research sample. Multiple regression model and statisctic descriptive is used to analysis data. The result indicates that the independent board of commissioners and audit committe do not effect firm’s value. Otherwise, managerial ownership, company’s size, return on equity, leverage, and earnings per share has effects firm’s value